Automatic Fire Detection Alarm Monitoring System in Balaraja District Based on Internet of Things - Ilamsyah, Ilamsyah; Tandilintin, Abert; Putra, Lingga Buana; Jawahir, Jawahir; Arribathi, Abdul Hamid (Journal Sensi: Strategic of Education in Information System, 2024)
The Balaraja Sub-District Office, as a Regional Apparatus Work Unit in Tangerang Regency, faces challenges in preventing fire disasters. Fires can cause significant loss of life, economic, and material losses. Currently, the sub-district lacks an effective prevention system, relying solely on post-fire handling measures. This research aims to design and implement a monitoring system and automatic fire detection alarm based on the Internet of Things (IoT) in the Balaraja Sub-District. This system is expected to detect fires early and provide rapid alarms to reduce losses. The research confines its scope to the Balaraja Sub-District, utilizing interviews and literature studies as data collection methods. The design method involves creating flowcharts and block diagrams, while the analysis method employs the PIECES framework. System testing is conducted using blackbox testing methods. The findings of this research are expected to contribute to the development of IoT technology for disaster mitigation in Indonesia, as well as enhancing the safety of employees and the surrounding community.